Health Benefits of Mediterranean Diet - Martini, Daniela (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Growing evidence shows that a dietary pattern inspired by Mediterranean dietprinciples is associated with numerous health benefits. A Mediterranean-typediet has been demonstrated to exert a preventive effect toward cardiovasculardiseases, in both Mediterranean and non-Mediterranean populations. Part ofthese properties may depend on a positive action toward healthier metabolism,decreasing the risk of diabetes and metabolic-syndrome-related conditions.Some studies also suggested a potential role in preventing certain cancers. Finally,newer research has showed that a higher adherence to the Mediterranean diet isassociated with a lower risk of cognitive decline, depression, and other mentaldisorders. Overall, a better understanding of the key elements of this dietarypattern, the underlying mechanisms, and targets, are needed to corroboratecurrent evidence and provide insights on new and potential outcomes.ThisSpecial Issue welcomes original research and reviews of literature concerningthe Mediterranean diet and various health outcomes:Observational studies onestablished nutritional cohorts (preferred), case-control studies, or populationsample on the association with non-communicable diseases;Level of evidenceon the association with human health, including systematic reviews and metaanalyses;Evaluation of application of Mediterranean diet principles in non-Mediterranean countries;Description of mechanisms of action, pathways, andtargets at the molecular level, including interaction with gut microbiota.